Entrepreneurship education and its gendered effects on feasibility, desirability and intentions for technology entrepreneurship among STEM students - Pergelova, Albena; Angulo-Ruiz, Fernando; Manolova, Tatiana; Yordanova, Desislava (My University, 2023)
This study aims to examine how entrepreneurship education influences intentions for starting a technology venture among science, technology, engineering and mathematics (STEM) students with particular attention to gender differences. This study builds on the model of entrepreneurial event and social role theory to assess the impact of entrepreneurship education on feasibility, desirability and intentions for technology entrepreneurship.
Keywords: entrepreneurship education; STEM; feasibility; desirability; entrepreneurial intentions; technology entrepreneurship; gender